Synthesis, characterization and in vitro antimicrobial activity of the Cu(II) and Fe(III) complexes with 1-cyclopropyl-6-fluoro-4-oxo-7-(piperazin-1-yl)-1,4-dihydroquinoline-3-carboxylic acid - Horozić, Emir; Cipurković, Amira; Ademović, Zahida; Kolarević, Lamija; Bjelošević, Demir; Zukić, Amila; Hodžić, Snježana; Husejnagić, Daria; Ibišević, Merima (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
1-Cyclopropyl-6-fluoro-4-oxo-7-(piperazin-1-yl)-1,4-dihydroquinoline-3-carboxylic acid (Ciprofloxacin, CFL) is a drug that belongs to the second generation of fluoroquinolone antibiotics with a wide range of effects on Gram-positive and Gram-negative bacteria. The bactericidal action of ciprofloxacin results from the inhibition of the enzymes topoisomerase II (DNA gyrase) and topoisomerase IV. In organism there is a possibility of interaction of CFL with biogenic elements in the blood, which could lead to the formation of complexes. This can cause change in the activity of antibiotics towards pathogenic microorganisms. The aim of this work was to investigate the interaction of CFL as ligand with the biological cations Cu(II) and Fe(III) in physiological condition. Synthesized complexes were characterized using IR spectroscopy and stereo-microscopy. Antimicrobial screening was performed on bacterial strains of Escherichia coli, Enterococcus faecalis, Staphylococcus aureus and Salmonella Enteritidis. The results of IR spectroscopy showed that the Cu(II) and Fe(III) complexes with CFL were formed through the oxygen donor atoms of carboxyl and carbonyl group of the ligand. The color and size changes of the crystal of the ligand and complexes were also clearly seen. Antimicrobial screening has shown that CFL and CFL complexes have similar antimicrobial activity against all tested strains. The Cu(CFL)2 complex showed better antimicrobial activity compared to the Fe(CFL)2(H2O)2 complex.